Factor Analysis of the Styrene Polymerization Kinetics. Statistical Verification of the Procedure (Global Journal of Science Frontier Research, 2015)
Introduction-Statistical verification of operations used earlier for kinetics experimental data treatment of the styrene suspension polymerization performed on the one of known kinetics model. Internal standard times matrix for different conversions found to have only two statistically significant eigenvalues. Therefore, they may be considerate as plains and easily described to give equation for its dependence from initial condition needed for dimensionless time scale definition. Conversion vectors dependence on the later forms sets of very closely curves. They may be considerate as stochastic realization of the one common curve what follows from its non parametric statistical comparison. Final single curve finds by uniting and sorting operation of its values. That operation gives one plain common curve described by empirical equation with small set of the empirical parameters needed, considerably less than in existing models. Procedure is convenient and robust.
Keywords: kinetics experimental; data treatment; statistical comparison